HUBUNGAN PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN REFLEKTIF DENGAN HASIL BELAJAR PADA MAHASISWA PSIKOLOGI FAKULTAS KEDOKTERAN UNIVERSITAS HASANUDDIN - Wahid Hasyim; Nurul Aisyah; Jauri Rakasiwi; Umniyah Saleh (Universitas Negeri Makassar, 2018)
This research aimed to determine whether there is a relationship between perception of reflective learning and learning outcome of student of Psychology Program of Hasanuddin University. The data were collected trough a perception of reflective learning in form of a likert scale that was developed based on the concept of perception and reflective learning. Outcome learning is reviewed based on grade point average (GPA) of the sample. Research sample consisted of 103 student of Psychology Program of Hasanuddin University. The Data were analyzed by using Product Moment Correlation with SPSS 21 for windows. The Result showed significant value of 0.010 which smaller than 0.05 or 0.010 <0.05 which indicate that there is positice relation between student perceptions of reflective learning with Grade Point Average (GPA) in Psychology Program of Hasanuddin University. Pearson Correlation value in this study is 0254, which means the relationship between the two variables is strong enough based on the criteria of relationship strength Sarwono (2006).